Prevention of Goods and Services Procurement Fraud and Its Implications on Good Government Governance - Cahyono Putro, Heru (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2022)
The fact that the number of corruption cases in Indonesia is increasing from year to year shows a phenomenon that has attracted the attention of a number of parties. Most of these cases involve the government, especially in terms of purchasing goods and services, which has implications for the development of effective governance. The purpose of this study was to examine the factors that influence fraud prevention in purchasing goods and services, as well as their influence on effective government management. The research data is primary data obtained through questionnaires and analyzed using SPSS IBM 26 software. The population of this study is employees Civil Servants (PNS) in the Mamberamo Raya Regency Regional Apparatus Organization (OPD) which has main tasks and functions in the procurement of goods and services as well as internal audits. The research sample is 70 samples using purposive sampling method. The results of the study show that internal control has no significant effect on the prevention of fraud in the procurement of goods and services, the effectiveness of internal audit has a significant effect on the prevention of fraud in the procurement of goods and services. Meanwhile, internal control and internal audit effectiveness have little effect on good government governance partially, and prevention of fraud in the procurement of goods and services has a significant effect on good government governance. The effect of internal control, internal audit on good government governance has a small effect if partially but if simultaneously it has a large influence while Internal control.